Gestão territorial e sustentabilidade socioambiental do povo Xavante : terra indígena de Marãiwatsédé, Bom Jesus do Araguaia-MT - Oliveira, Raimundo Nonato Silva de (2015)
ABTRACT - The Indigenous Land (TI) Xavante of Marãiwatsédé is under the political jurisdiction of Bom Jesus do Araguaia -MT. For a long time the Xavante people occupied their territory in the traditional way. The political, economic, social, cultural they changed the life of society. These changes affected the territory and the lives of Xavante of Marãiwatsédé, observed changes in lifestyle, in relationship to the land, social relations, food, traditions and other aspects influencing the traditional way of occupation of the territory. In that situation lies the central issue of research of the research that has as main objective the investigation of agents that influence the Indigenous Land Management Marãiwatsédé and environmental sustainability of the Xavante people. The specific objectives are: To reflect on the key actors that contribute to land management in the village of Marãiwatsédé. Understand the problems of indigenous issues in the State of Mato Grosso in Paradigm Perspective Agrarian Question ( PQA ), investigate the relationship between teachers and the local community; Knowing the everyday knowledge of the elders related to the territory; Evaluate the possibility of contribution of Indigenous education (formal) in land management. Evaluate the possibility of contribution of Indigenous education (formal) in land management. The methodological contributions reside in qualitative research and direct observation procedures, interviews, oral history and documentary photographs and analysis. The observation has contributed to understanding how social, economic and institutional processes materialize in community and land management. Interviews with the elders, elders and teachers (as), were important to understand how the community uses local resources, with a view to economic dynamism and improving the quality of life. The analysis of documents such as plans for Territorial and Environmental Management of Indigenous Lands (PGTAs) and PPP - Pedagogical Political Project of the State School Marãiwatsédé were important to realize the materiality of these management mechanisms in the Indigenous Land. And finally, the photographs recorded moments of everyday life and how Chavantes dominate the territory and create new territoriality. The results indicate that the environmental impacts on the territory from the 1960s, the incorporation of extensive farming has intensified, especially since the 1980s, with the increasing deployment of grain for export , especially soybeans. The Xavante people of Marãiwatsédé goes through a planning process resumed. Despite efforts to maintain their traditional way of life, based mainly on agricultural crops (corn, beans, cassava) coexist with government policies that encourage them to adopt economic practices, especially the slash and burn agriculture and cattle breeding. Environmental degradation result of livestock and agricultural monoculture, surrounding and inside the Xavante territory, strongly decreases the stock of wildlife, used both for food and for the rituals of the culture, especially the marriage. The land required for subsistence Xavante encompassed large tract of land where the exploited groups in search of food, hunting and gathering. Currently this standard excursions disappeared due to the reduction of the land. This has influenced the way of life of the village Xavante of Marãiwatsédé, agriculture coexists with the transformation of mechanization. Therefore, the Xavante seek other perspectives of life, the resumption of land, an area of 165 hectares, represents a breakthrough in the reconquest of its territory, but at the same time have a number of dilemmas to be thought of by the community, such as environmental degradation, scarcity water, food, health infrastructure. The construction of a new village in the area gains strength in the community however is being discussed with the National Indian Foundation (FUNAI) - Brasilia. In this process the knowledge of the elders and formal education have contributed to the recognition of the territory and development work with the community to ensure environmental sustainability.